2010
DOI: 10.1017/s0317167100010799
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Error in Neuropathology Intraoperative Diagnosis

Abstract: Specialists institute a variety of diagnostic audits to identify areas of weakness and to optimize clinical performance [1][2][3][4][5] . In pathology, one common diagnostic event well-suited to this type of analysis is the intraoperative consultation where touch, smear and frozen section preparations have long been used to assist surgical decision making [6][7][8][9] .Neurosurgeons incorporate a neuropathologist's interpretation into the surgical plan through intraoperative consultations on small biopsies 5,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The accuracy of the SRH-based neuropathological diagnosis from the first samples analyzed at our institution (including the very first) was 87.7% (Fig. 3a ), which was close to the lower bound of the range of diagnostic accuracy (89–98%) reported for intraoperative frozen section neuropathological diagnosis [ 15 , 25 , 26 ]. It should be noted that the investigators had no prior experience with sample preparation specific to Raman imaging or SRH image interpretation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The accuracy of the SRH-based neuropathological diagnosis from the first samples analyzed at our institution (including the very first) was 87.7% (Fig. 3a ), which was close to the lower bound of the range of diagnostic accuracy (89–98%) reported for intraoperative frozen section neuropathological diagnosis [ 15 , 25 , 26 ]. It should be noted that the investigators had no prior experience with sample preparation specific to Raman imaging or SRH image interpretation.…”
Section: Discussionsupporting
confidence: 73%
“…3e ). Sampling errors were reported to be another major source of error in the conventional intraoperative neuropathological diagnosis [ 15 ]. In this study, spatially similar but not identical samples were processed in parallel for SRH and H&E. It is possible that distinct parts of the tumor were submitted to either method yet not to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analysis showed that a more experienced clinician was significantly less likely to generate a false positive referral. This seems logical, and improvement in diagnostic proficiency with increasing experience has been shown before across various medical disciplines, 28 , 29 , 30 but it is a novel finding for optometry. If an inexperienced optometrist is unsure of a diagnosis, it would be unfair and potentially dangerous to criticise or discourage referral as there is a natural learning curve with experience in any profession.…”
Section: Discussionmentioning
confidence: 79%